How is Foreign Language Learning Implemented Online? The Case of Indonesian Language for Foreign Speaker - Susandi, Susandi; Sumarsilah, Siti; Suyitno, Imam; Nurzafira, Istiqomah; Tamphu, Sainee (FKIP Universitas Lampung, 2022)
How is Foreign Language Learning Implemented Online? The Case of Indonesian Language for Foreign Speaker. Objectives: this article aims to describe the platforms commonly used in learning and teaching Indonesian for foreigners online, the problems encountered, and the solutions. Methods: the researcher employed qualitative research. In obtaining information from three resource persons who teach at the State University of Malang, an in-depth interview technique was used with the aim of obtaining comprehensive information. Findings: The results show that there are four types of digital platforms that are often used: Zoom, Google Classroom, WhatsApp, and UKBIPA. Meanwhile, the problems faced are divided into two categories: technical and substance. Meanwhile, the solution proposed by the teacher is to improve digital skills and make maximum use of authentic sources spread across various social media platforms. Conclusion: online learning using a digital platform has advantages and disadvantages, to overcome these shortcomings, collaborative efforts from various parties are needed so that foreign students can achieve communicative competence even though learning is carried out online. Keywords: BIPA, digital platform, second language.DOI: http://dx.doi.org/10.23960/jpp.v12.i3.202207